Nurse-Led Digital Perioperative Care to Improve Wound Healing, Pain, and Mobilisation After Caesarean Section in Ethiopia: A Randomised Control Trial - Egor, Dorian Einar; Carlos, Boryslaw; Carmen, Elen Britta (Global Indonesia Health Care (GOICARE), 2026)
Background: Post-caesarean wound complications and slow recovery remain a major burden in low-resource maternity settings, while evidence on nurse-led digital perioperative care to improve wound healing is limited. Purpose: This study aimed to test the effect of a nurse-led app-based perioperative programme on post-caesarean wound healing among Ethiopian women. Methods: In a randomised controlled trial at Yanet General Hospital, Ethiopia (2024), we enrolled 148 women undergoing elective caesarean section, randomised to standard care versus standard care plus C-Care with dietary support; the primary outcome was WH-PAT score at day 14. Results: Among 148 randomised women, 62.2% in the C-Care group versus 40.5% in standard care achieved complete wound healing by day 14 (risk difference 21.6%, 95% CI 6.1–37.1); mean WH-PAT scores were higher in the intervention group, and early pain and time to mobilisation were significantly improved. Conclusion: A nurse-led app-based perioperative programme improved key recovery outcomes after elective caesarean section in this low-resource setting. Finding support for integrating digital nursing follow-up into post-caesarean care pathways and testing scalability. Relevance to clinical practice: This study shows that a nurse-led, app-based perioperative programme can be integrated into routine caesarean care to improve wound healing, pain, and mobilisation. Obstetric nurses can use C-Care to standardise education, monitor recovery remotely, triage high-risk women earlier, and extend evidence-based care beyond discharge.